Magnetically recoverable Fe3O4-lignin nanocomposites as a sustainable Fenton-like catalyst for dye degradation - Kemprai, Rahul; Sut, Nayana; Hazarika, Swapnali; Pal, Shibam; Bhuyan, Balin Kumar; Gogoi, Parikshit (Chemical Physics, 2026)
Fenton chemistry is a highly effective advanced oxidation processes (AOPs) for degrading organic pollutants in wastewater. However, conventional homogeneous Fenton systems face key drawbacks such as limited pH range, sludge formation, and poor recyclability. To address these challenges, iron oxide-based composites are used as efficient heterogeneous Fenton catalysts due to their strong redox activity and stability. In this work, Fe3O4-lignin nanocomposites were synthesized by a simple co-precipitation method and characterized using analytical techniques. The composites showed excellent performance, degrading 93% of MB far higher than pure Fe3O4 (48%). The enhanced activity stems from lignin's electron-donating and surface functional groups, which boost enhance Fe2+/Fe3+ cycling and promote center dot OH generation. A plausible degradation mechanism highlighting the synergistic role of lignin is proposed. The nanocomposites maintained high efficiency over five cycles, showing strong stability and magnetic recovery, making Fe3O4-lignin a promising and low-cost catalyst for wastewater treatment.
Keywords: Catalytic activity; Co-precipitation; Dye degradation; Fenton chemistry; lignin